Implementation of al-Ma'un Theology in the concept of educational equality in Indonesia (Study of Ahmad Dahlan's Thoughts in the Social Aspects of Education) - Daib Insan Labib, Muhammad Alfreda (Proceeding International Conference on Religion, Science and Education, 2024)
This article discusses how the process of implementing Ahmad Dahlan's al-Ma'un theology became a manifesto for the concept of education in the Muhammadiyah Association. Based al-Ma'un theological philanthropy, researchers will present a study on how Ahmad Dahlan way’s eradicated poverty and ignorance that shackled Indonesian society. The study aspect in this article will collaborate how western social science and the social sciences pioneered by Ahmad Dahlan became a new force in forming an egalitarian society or in Marxist language a classless society. The method used in this paper is qualitative, namely a method that uses the literature that has been collected as a reference source. In processing data, researchers use descriptive analysis methods, namely by presenting the data that has been collected and then analyzing it to achieve the objectives of the research. This article starts from three basic questions, First, What is Ahmad Dahlan's paradigm and direction of thought? Second, What is meant by social theology and al-Ma'un's theology? Third, How is the concept of education and implementation of al-Ma'un's theology in equalizing education in Muhammadiyah. The results of this study show that; 1). Among the directions of Ahmad Dahlan's thinking is to realize Muslims who return to al- Qur’an and Sunnah. 2). Social Theology and al-Ma'un have interconnected similarities and differences. 3). The concept of education and implementation of al-Ma'un Theology in equalizing education in Muhammadiyah can be done in various ways. This includes providing subsidies and educational scholarships for those in need.